(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article is aimed at a comprehensive analysis of the role of resource taxes in the transition of the country’s economy to a "green" model within the framework of the " Uzbekistan - 2030" strategy, their fiscal and incentive functions, and their impact on investment attractiveness. The study assesses the economic efficiency of resource taxes - subsoil use, water resource use, and land tax based on statistical data for 2023-2025. Within the framework of the "Double Dividend" hypothesis, mechanisms for ensuring a balance between environmental protection and economic growth are studied.